Shifting genetic patterns in anencephaly and spina bifida. Issue 2 (April 1978) - Janerich, D T; Piper, J
Abstract : The long-term decline in the incidence of the neural tube malformations, anencephaly and spina bifida (ASB), ended in the mid-1950's in New York State. Since that time, the rate of these birth defects has remained between 1 and 1.5/1000 births. In this low incidence population, we tested the basic tenets which support a genetic aetiology. We found that the full sib recurrence rate (1.8%) was higher than the half sib recurrence rate (0.8%) and the twin concordance rate (6.8%) was higher than the full sib recurrence rate. We found the incidence of ASB in twins to be the same as the incidence of ASB in singletons. Our findings are compatible with polygenic inheritance aetiology for ASB. The genetic molecular pathway of these birth defects may be identifiable through biochemical screening of families with one or more ASB children.